2022
DOI: 10.1007/s10668-022-02320-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental efficiency under weak disposability: an improved super efficiency data envelopment analysis model with application for assessment of port operations considering NetZero

Abstract: Due to ports have rapidly been expanding, air pollution resulted from port operations has expansion and become a persistent concern for environmentalist and policy makers. The objective of this paper is to measure the environmental efficiency of ports in Korea. The main characteristic of the environmental efficiency assessment problem is that undesirable output of carbon dioxide (CO2) emissions and exogenous fixed input of the terminal area of ports should concurrently be considered. By analysing the impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…Taleb et al (2022) used the super-efficiency SBM model to effectively distinguish efficient and inefficient ports in South Korea and rank their efficiency. The researchers believe that the proposed method has certain applicability to 19 ports in South Korea [7].…”
Section: Introductionmentioning
confidence: 92%
“…Taleb et al (2022) used the super-efficiency SBM model to effectively distinguish efficient and inefficient ports in South Korea and rank their efficiency. The researchers believe that the proposed method has certain applicability to 19 ports in South Korea [7].…”
Section: Introductionmentioning
confidence: 92%
“…Seaports are also recommended to improve production efficiency while ensuring sustainable development by forecasting container demand and making long-term port expansion plans based on such a market. Taleb et al [26] determined the environmental efficiency of 19 container ports in South Korea using the super SBM approach. The results showed that undesirable outputs (i.e., CO 2 emissions) should be reduced to improve seaport environmental efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study indicated that only the USA ensures the environmental efficiency in energy R&D expenditures among OECD countries. The similar studies have examined environmental efficiency for different service sectors such as airline Environmental efficiency of buildings firms, ports and sewage treatment plants by using a directional distance function DEA, SBM DEA and window-based DEA, respectively (Xu et al, 2021;Taleb et al, 2022;Fallahiarezoudar et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%